Evaluation of the Appendicitis Inflammatory Response Score against Alvarado Score in Diagnosis of Acute Appendicitis - Karki, O.B.; Hazra, N.K. (Kathmandu University Medical Journal, 2020)
Background Patients presenting with suspected appendicitis pose a diagnostic challenge. Various scoring systems have been designed to aid in the clinical assessment of these patients. Widely applied was Alvarado score and best performed in validating studies, but was observed with few drawbacks. Appendicitis inflammatory response (AIR) score was designed to overcome the drawbacks associated with the implementation of Alvarado scoring system. Objective The main objective of this study was to evaluate the Appendicitis inflammatory Response Score and compare its performance in predicting risk of appendicitis with the Alvarado score. Method Appendicitis inflammatory response score and Alvarado scores were calculated prospectively on patients suspected of acute appendicitis presenting to Manipal Teaching Hospital, Pokhara, Nepal between July 2017 and June 2019. Diagnostic performance of the two scores was compared. Statistical analysis was done using SPSS 21 and p value < 0.05 was considered significant. Result The study included 217 patients with 109 (50.2%) males and 108 (49.8%) females. The mean age of patients was 25.77±15.54. The results analyzed showed better sensitivity of Appendicitis Inflammatory Response score (96.91%) as compared to 94.30% of Alvarado score. The positive and negative predictive values of Alvarado score were 74.87% and 50%, as compared to 79.70% and 72.20% for AIR score. Furthermore, the area under receiver operating curve of the appendix inflammatory response score was better (0.701) than that of Alvarado score (0.580). Conclusion Appendicitis Inflammatory Response (AIR) scoring performed well and more accurate than Alvarado scoring system with high specificity and high negative predictive value preventing negative appendectomies.